The Effectiveness of the Quantum Teaching Learning Model on Islamic Re-ligious Education (PAI) Learning Outcomes at State Elementary School 1 Katobengke - Fatma, Debi Yanti; Maudin, Maudin; Ridwan, Muhammad (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
This study aims to analyze the effectiveness of the Quantum Teaching learning model on the learning outcomes of Islamic Religious Education (PAI) at Elementary School 1Katobengke. This study uses a qualitative method with the object of research being 27 fifth grade students, consisting of 15 male students and 12 female students, and 1 PAI teacher. The instruments used in this study were observation, interviews, and documentation. The study was conducted in two cycles with two meetings in each cycle. The results of the study showed a significant increase in student learning outcomes between cycle I and cycle II. The average student score increased from 71.1 in cycle I to 77.59 in cycle II, with the percentage of student learning completion reaching 85.19% in cycle II. The application of the Quantum Teaching model succeeded in creating an active, enjoyable learning atmosphere, increasing student interest, and motivating them to be more involved in learning. Thus, the Quantum Teaching model has proven effective in improving Islamic Religious Education learning outcomes at Elementary School 1Katobengke and can be used as an alternative learning method that is more interesting and meaningful.